Angiolymphoid hyperplasia with eosinophilia and Kimura's disease – a clinical and histopathological comparison. (19th December 2013) - Buder, Kristina; Ruppert, Sabrina; Trautmann, Axel; Bröcker, Eva‐Bettina; Goebeler, Matthias; Kerstan, Andreas
Summary Angiolymphoid hyperplasia with eosinophilia (ALHE) is a benign vascular neoplasm mainly affecting middle‐aged women. Lesions typically affect the head and neck region. ALHE is considered a distinct disease entity different from Kimura's disease, a benign reactive lymphoid proliferation that is predominantly seen in young Asian men although it can affect all ethnic groups. In contrast to ALHE, Kimura's disease is typically associated with peripheral blood eosinophilia, increased serum IgE and lymphadenopathy. Several case reports suggest an overlap between ALHE and Kimura's disease. We review the current literature and discuss whether AHLE and Kimura's disease might represent two extreme variants of the same disease entity.